The impact of international entrepreneurial orientation and open innovation on the international performance of Chinese SMEs in cross-border e-commerce: A quantitative study - Xue, Chen; Mansor, Mohd Najib (Edelweiss Applied Science and Technology, 2025)
The advent of digital technologies and the intensification of globalization have driven the transformation of cross-border e-commerce (CBEC) into a disruptive force in global trade, effectively overcoming the spatial constraints of traditional business models [1, 2]. In this evolving environment, the present research investigates how international entrepreneurial orientation (IEO) influences the international performance (IP) of Chinese SMEs engaged in CBEC, with a specific focus on the mediating effect of open innovation (OI). Grounded in resource-based theory, both IEO and OI are conceptualized as strategic intangible resources that contribute to competitive advantage in global markets. A total of 289 SMEs from Yiwu, China—a recognized hub for CBEC—participated in a cross-sectional survey and provided primary data. Mediation testing was carried out using SPSS 30.0 and the PROCESS Macro (Model 4), applying 5,000 bootstrap iterations. The findings indicate that IEO significantly enhances IP both directly and indirectly via OI. These results underscore the importance of cultivating open innovation capabilities—particularly in sourcing and applying external knowledge—to convert entrepreneurial intent into successful internationalization outcomes. The study offers practical implications for digitally oriented SMEs in emerging economies and contributes to ongoing scholarship in international entrepreneurship and innovation management.